Laparoscopic Curative Resection for Rectal Cancer: A Cohort Study on Long-term Outcome. Issue 5 (October 2018) - Portale, Giuseppe; Valdegamberi, Alessandro; Cavallin, Francesco; Morabito, Alberto; Frigo, Flavio; Fiscon, Valentino
Abstract : The aim of the present study was to evaluate the long-term results of laparoscopic curative resection for rectal cancer. We included all patients who underwent laparoscopic curative resection for rectal cancer from June 2005 to September 2015. A total of 159 patients were included; 33.9% received neoadjuvant chemoradiotherapy. Thirty-day mortality and morbidity rates were 0.6% and 26.4%, respectively. Pathologic stage was 0 in 12%, I in 39%, II in 24.5%, and III in 24.5%. The median number of lymph nodes harvested was 16. In 5% of patients, mesorectal excision was incomplete. Median follow-up was 59 months. Overall 5-year survival was 80%. Multivariable analysis identified older age, higher Charlson Comorbidity Index, advanced tumor stage, and postoperative morbidity as independent risk factors for overall/disease-free survival. Local/distant recurrence rate was 4.4%/17.6%. Deaths during follow-up were 33/159 (20.8%): cancer related 54.6% and non cancer related 45.4% of patients. Laparoscopic curative resection for rectal cancer can yield prolonged survival and low recurrence.